Transmissivity and reectivity of a transverse-electric polarized wave incident on a microcavity containing strongly coupled excitons with in-plane uniaxially oriented transition dipole moments - Taylor, R; Le Roux, F; Bradley, D (Wiley, 2020)
This work examines the reflectivity and transmissivity of a transverse‐electric (TE) polarized wave incident on a microcavity containing strongly coupled excitons with in‐plane uniaxially oriented transition dipole moments, and a different interpretation to a previous report is presented. The propagation of the electric field inside the cavity is discussed, and a distinction is made between two different physical cases: the first, previously observed, and the second, which enables the interpretation of measurements carried out on a microcavity containing an oriented layer of liquid‐crystalline poly(9,9‐dioctylfluorene). In all cases, the reflected and transmitted electric fields derive from photons leaking parallel and perpendicular to the transition dipole moment orientation.